Analysis of random events in physical and chemical processes flowing in materials of semiconductor products under external influences and thermal aging - Milenin, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
It has been proposed to consider physical and chemical processes in materials of semiconductor products under external influences and thermal aging as flows of the random events. The mathematical analysis of random events in the physical and chemical processes has been presented. The theoretical results have been applied to the analysis of a number of processes.